2018
DOI: 10.1111/sjpe.12175
|View full text |Cite
|
Sign up to set email alerts
|

The real peso–dollar rate and US–Mexico industry trade: an asymmetric analysis

Abstract: In an attempt to improve upon previous analyses and find further evidence for exchange rate theories such as the 'J-curve', numerous studies have introduced novel econometric approaches that might help uncover significant results through disaggregation and nonlinearity. This study applies the nonlinear cointegration method of Shin et al. (2014) to US-Mexican trade balances in 91 individual industries. While the linear model yields support for the 'J-curve' effect in 16 industries, the nonlinear model raises th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The list includes Bahmani‐Oskooee and Baek () who included 79 industries that trade between Korea and the U.S.; Bahmani‐Oskooee and Rahman () who dealt with 11 industries that trade between Bangladesh and the U.S.; Bahmani‐Oskooee and Saha () who considered the case of India and the U.S. and included 68 industries; and finally, Bahmani‐Oskooee et al . () who considered 91 industries between Mexico and the U.S.…”
Section: The Estimation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The list includes Bahmani‐Oskooee and Baek () who included 79 industries that trade between Korea and the U.S.; Bahmani‐Oskooee and Rahman () who dealt with 11 industries that trade between Bangladesh and the U.S.; Bahmani‐Oskooee and Saha () who considered the case of India and the U.S. and included 68 industries; and finally, Bahmani‐Oskooee et al . () who considered 91 industries between Mexico and the U.S.…”
Section: The Estimation Resultsmentioning
confidence: 99%
“…Following the literature and specifically Bahmani‐Oskooee et al . () we begin with the following reduced form trade balance model:LnTBSF,ti=a+bLnYUS,t,+cLnYSF,t+dLnREXnormalt+εt…”
Section: The Models and Methodsmentioning
confidence: 99%
“…However, the net benefit of depreciation can only be positive if the elasticities of export and import sum up to a value greater than unity, i.e. the Marshall-Lerner condition (see Bahmani-Oskooee Ratha, 2004 or most recently Bahmani-Oskooee and Saha, 2017; Bahmani-Oskooee et al , 2018 for interesting insights). Hence, on the depreciation, there is mixed evidence supporting the role of depreciation in improvements in trade balances (see Bahmani-Oskooee, 1991a, b; Bahmani-Oskooee and Ratha, 2004; Bahmani-Oskooee and Hegerty, 2010; Bahmani-Oskooee et al , 2013, 2016, 2018; Yildirim and Ivrendi, 2016, Bahmani-Oskooee and Saha, 2017) and also indicating a lack of evidence on such a nexus, for instance, seminal work by Rose and Yellen (1989) and Rose (1991).…”
Section: Nexus Exchange Rate Misalignment and Trade Imbalancementioning
confidence: 99%
“…the Marshall-Lerner condition (see Bahmani-Oskooee Ratha, 2004 or most recently Bahmani-Oskooee and Saha, 2017; Bahmani-Oskooee et al , 2018 for interesting insights). Hence, on the depreciation, there is mixed evidence supporting the role of depreciation in improvements in trade balances (see Bahmani-Oskooee, 1991a, b; Bahmani-Oskooee and Ratha, 2004; Bahmani-Oskooee and Hegerty, 2010; Bahmani-Oskooee et al , 2013, 2016, 2018; Yildirim and Ivrendi, 2016, Bahmani-Oskooee and Saha, 2017) and also indicating a lack of evidence on such a nexus, for instance, seminal work by Rose and Yellen (1989) and Rose (1991). In specific to China, Bahmani-Oskooee and Wang (2006) while analysing the impact of real depreciation on China reported that with a few of its trading partners there was favourable impact including the USA.…”
Section: Nexus Exchange Rate Misalignment and Trade Imbalancementioning
confidence: 99%
See 1 more Smart Citation